Assessment of Life Cycle Impacts and Integrated Evaluation Concept for Equipment Investment - Fleschutz, Timo; Abdul Rahman, Azrul Azwan; Harms, Robert; Seliger, Günther (2010)
Industrial companies are nowadays confronted with both economic challenges regarding cost efficiency based on the globalization and shortened product life cycles as well as societal and ecological challenges to support a sustainable development. The paper will present the results of life cycle assessment studies for assembly equipment and industrial robots. A simulation based approach for the estimation of the energy consumption during the use phase will be demonstrated on a case study. A concept for the evaluation of assembly equipment combining both a triple bottom line and flexibility is proposed and explained.